A systematic review of knowledge, attitude and practice of pharmacogenomics in pediatric oncology patients - Moore, Claire; Lazarakis, Smaro; Stenta, Tayla; Alexander, Marliese; Nguyen, Rachel Phan; Elliott, David A.; Conyers, Rachel (Pharmacology research & perspectives, 2023)
Pharmacogenomics remains underutilized in clinical practice, despite the existence of internationally recognized, evidence‐based guidelines. This systematic review aims to understand enablers and barriers to pharmacogenomics implementation in pediatric oncology by assessing the knowledge, attitudes, and practice of healthcare professionals and consumers. Medline, Embase, Emcare, and PsycINFO database searches identified 146 relevant studies of which only three met the inclusion criteria. These studies reveal that consumers were concerned with pharmacogenomic test costs, insurance discrimination, data sharing, and privacy. Healthcare professionals possessed mostly positive attitudes toward pharmacogenomic testing yet identified lack of experience and training as barriers to implementation. Education emerged as the key enabler, reported in all three studies and both healthcare professionals and consumer groups. However, despite the need for education, no studies utilizing a pediatric oncology consumer or healthcare professional group have reported on the implementation or analysis of a pharmacogenomic education program in pediatric oncology. Increased access to guidelines, expert collaborations and additional guidance interpreting results were further enablers established by healthcare professionals. The themes identified mirror those reported in broader pediatric genetic testing literature. As only a small number of studies met inclusion criteria for this review, further research is warranted to elicit implementation determinants and advance pediatric pharmacogenomics.